ANALISIS YURIDIS TENTANG INDEPENDENSI BANK INDONESIA DITINJAU DARI UNDANG-UNDANG NOMOR 3 TAHUN 2004 PERUBAHAN ATAS UNDANG-UNDANG NOMOR 23 TAHUN 1999 TENTANG BANK INDONESIA - Fredi Alsabah, Febriansyah; Dawisni Manik Pinatih, Siluh Putu (Kertha Semaya : Journal Ilmu Hukum, 2014)
Independence of Bank Central of Indonesia has set up in section 4 article (2) The Act Number 3 Year 2004 alteration from The Act Number 23 Year 1999 about Bank Central of Indonesia. The purpose of this research is to know and analyze about Independence of Bank Central of Indonesia consider from The Act Number 3 Year 2004 alteration from The Act Number 23 Year 1999 about Bank Central of Indonesia. From analyze it, we can know clearly the meaning of section 7 article (2) The Act of Bank Central of Indonesia. The method used in this research is the use of normative legal research by statute approach.The conclusion from this research is the meaning of section 7 article (2) The Act of Bank Central of Indonesia have characteristic consideration, not by persistent. It’s because the government have the duty of give protection to Indonesian people interrelated monetary policy of Bank Central of Indonesia. The Intervention in monetary policy of Bank Central of Indonesia by the government is not have characteristic persistent, intimidation, and threat, so Bank Central of Indonesia can ignore consideration of the government public policy in economy part.
Keywords: Independence, Bank Central of Indonesia, Intervention